2015
DOI: 10.3892/etm.2015.2417
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between serum levels of C-reactive protein and infant pneumonia: A meta-analysis

Abstract: Abstract. Experimental data imply that serum C-reactive protein (CRP) is a marker of general systemic inflammation, and inflammation may have a role in the development of pneumonia. The aim of the present study was to investigate the associations of serum CRP levels in infant patients with pneumonia by meta-analysis. The Science Citation Index, Cochrane Library, PubMed, Embase, CINAHL, Current Contents and two Chinese (CMB and CNKI) databases were searched. Studies were pooled and standard mean difference (SMD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…It has been suggested that CRP may be one of the best single tests for the early detection of pneumonia in children and could be widely used as marker of infection . The main results of the meta‐analysis by Xiao et al showed that serum CRP levels of newborn infants with pneumonia were higher than those of healthy subjects, suggesting that increasing levels of CRP may indicate pneumonia in newborn infants …”
Section: Introductionmentioning
confidence: 99%
“…It has been suggested that CRP may be one of the best single tests for the early detection of pneumonia in children and could be widely used as marker of infection . The main results of the meta‐analysis by Xiao et al showed that serum CRP levels of newborn infants with pneumonia were higher than those of healthy subjects, suggesting that increasing levels of CRP may indicate pneumonia in newborn infants …”
Section: Introductionmentioning
confidence: 99%
“…In addition, a meta-analysis demonstrated that there were correlations between serum levels of CRP and pneumonia in infants. 37 It has also been reported that serum CRP can be used as a biomarker for evaluating the efficacy of macrolides in macrolide-resistant MPP. 28 In our study, there was no correlation between levels of CRP and IL-17A.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have demonstrated a strong association between an increase in CRP levels and the risk of severe pneumonia in children, as shown in one meta-analysis 23 . Elevated CRP levels in pneumonia patients often indicate a more aggressive inflammatory response and a higher burden of infection.…”
Section: Discussionmentioning
confidence: 89%